The Influence of the Inquiry Learning Model on Critical Thinking in Science Learning in Grade V Elementary School - Prasanti, Ni Putu Putri; Suniasih, Ni Wayan (Thinking Skills and Creativity Journal, 2023)
Students’ critical thinking skills are still low, especially in science lessons. This study aims to analyze the effect of the Inquiry Learning Model on the critical thinking skills of students in science subjects in fifth grade elementary school students. This type of research is a quasy experiment with the Nonequivalent Control Group Design. The population of this study were all 160 students of fifth grade elementary school with a sample of 34 students in the experimental group and 29 students as the control group which was determined using the Cluster Random Sampling Technique. Collecting research data using the description test method consisting of 9 valid questions. Research data were analyzed using descriptive statistical analysis techniques and inferential statistical analysis techniques and then analyzed using the t-test (polled variance formula). The results showed that t-count was 3.923 and ttable was 1.999 at a significance level of 5% (α equal to 0.05) with degrees of freedom (dk) equal to 61 so that Ho was rejected. It was concluded that there was a significant influence from the application of the Inquiry learning model on critical thinking skills in science lessons for fifth grade elementary school students. This research makes a new contribution in understanding the effectiveness of the inquiry learning model in increasing critical thinking in fifth grade students.